High Performance Liquid Chromatography Fingerprinting Technology of the Commonly-used Traditional Chinese Medicine Herbs. - Poon, Ong Seng (World Scientific, 2012)
This book provides a comprehensive and up-to-date account of the HPLC technology and fingerprints of commonly-used Chinese herbs. It contains HPLC fingerprints of over 40 traditional Chinese medicinal herbs and details of their sources, production and quality control. The book provides a practical review of the techniques, relevant materials, and the particular demands for using HPLC in traditional Chinese medicinal herb applications. It also covers HPLC methods used to analyze the herbs. High-performance liquid chromatography (HPLC) is increasingly used in the field of traditional Chinese med.